Liver elasticity measurement before and after biliary drainage in patients with obstructive jaundice: a prospective cohort studya prospective cohort study. Issue 1 (December 2016) - Kubo, Kimitoshi; Kawakami, Hiroshi; Kuwatani, Masaki; Nishida, Mutsumi; Kawakubo, Kazumichi; Kawahata, Shuhei; Taya, Yoko; Kubota, Yoshimasa; Amano, Toraji; Shirato, Hiroki; Sakamoto, Naoya
Abstract Background Obstructive jaundice has been reported to influence liver elasticity, independent of liver fibrosis. The aim of our prospective study was to evaluate the changes in liver elasticity, before and after biliary drainage, in patients with obstructive jaundice, and to evaluate the correlation between elasticity measures and serum markers of liver fibrosis. Methods This is a prospective cohort study of 20 patients with obstructive jaundice. Liver elasticity was assessed by Transient Elastography (TE) and Virtual Touch™ Quantification (VTQ). Serum total bilirubin (T-Bil) level was measured before biliary drainage (Day 0), with measures repeated at 2 days (Day 2) and 7 days (Day 7) after biliary drainage. Serum levels of the following markers of liver fibrosis were also obtained on Day 0 and Day 7: hyaluronic acid (HA), procollagen-III-peptide (P-III-P). Results T-Bil, TE, and VTQ for the left (VTQ-L) and right (VTQ-R) lobes of the liver were all elevated before biliary drainage, with respective levels, measured at Day 0, of 11.9 ± 1.5 mg/dl, 12.1 ± 0.9 kPa, 2.23 ± 0.10 m/s, and 1.85 ± 0.10 m/s. All values decreased on Day 7 after drainage: T-Bil, 4.7 ± 1.0 mg/dl (P < 0.001); TE, 7.6 ± 0.6 kPa (P < 0.001); VTQ-L, 1.53 ± 0.08 m/s (P < 0.001); and VTQ-R, 1.30 ± 0.05 m/s (P < 0.001). Similar changes were observed in serum markers of liver fibrosis. Liver elasticity measures correlated with serum levels of T-Bil, P-III-P, and HA (r = 0.35-0.67, P < 0.001). Conclusions This study confirmed decreases in liver elasticity, measured by TE and VTQ, after biliary drainage. Measures of liver elasticity correlated to levels of T-Bil and serum markers of liver fibrosis. (UMIN ID: UMIN00001284313). Trial registration Registration number: University Hospital Medical Information Network (UMIN) Clinical Trials Registry (UMIN ID:UMIN00001284313 ); Registration date: 2014-01-14.